Pengaruh Brand Image,Personal Branding Endorser Dan Customer Experience Terhadap Minat Beli Bolosego Di Toko Camilan Cibubur - Rishawa, Dena; Nasution, Yuslinda (Jurnal Manajemen, 2025)
This study aims to determine the influence of Brand Image, Endorser Personal Branding, and Customer Experience on purchase intention of bolosego product at Toko Camilan Cibubur. The study was conducted quantitatively with 40 respondents, using non – probability sampling techniques and multiple linear analysis using SPSS 26. The results showed that all three variables simultaneously influenced purchase intention. However partially, only Customer Experience had a significant effect, while Brand Image and Endorser Personal Branding did not. The coefficient of determination of 22,8% indicates that purchase intention is explained by these variables, while 78,2% is influenced by other factors outside this study. Keywords: : Brand Image,Personal Branding Endorser,Customer Experience